ANALISIS PENGARUH INVESTASI, INDEKS PEMBANGUNAN MANUSIA DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI (Studi Pada Sumatera Barat Tahun 2010-2019) - Syofria Meidona; Virell Prastama; Elsa Fitri Amran (AL-ITTIFAQ: Jurnal Ekonomi Syariah, 2021)
This study aims to determine how to analyze the effect of investment,  human development index and labor on the economic growth of West Sumatra in the 2010-2019 period. The data used in this study is secondary data, namely panel data consisting of time series data over a period of ten years, namely 2010-2019.  The method used for sampling  this research using saturated  sampling. This study uses the SPSS program  version 23. Based on the hypothesis  testing  carried out using multiple linear regression analysis with the results Y = 20.139 +0.001 X1 - 0.208 X2 - 0.017 X3 at a significance level of 0.05 on the three variables, with an investment value of tcount 0.774 <ttable1,943, sig value 0.468>  0.05 indicates  a positive  direction,  HDI tcount  -3.360>  t table 1.943,  sig value 0.015 <0.05 indicates  negative direction, and Labor tcount 0.774 <t table 1.943, Sig value 0.58>  0.05 indicates  Negative  direction,  the results  of this study prove  that partially  the human development index has an effect on economic growth, while the investment and labor variables have no  effect  on  economic  growth.  The  results  of  simultaneous   research   on  investment,   human development  index,  and  labor  have a significant  effect  on economic  growth  with tcount  5,137> ttable 4,76, sig value 0.043 <0.05.